Simple Experimental Setups for Observing Wave-particle and Entanglement-separability Superpositions - An, Nguyen Ba (Communications in Physics, 2016)
It has been long believed that waveand particle cannot be superposed. Recently, however, modern quantumtechniques have allowed one to prepare photon wave-particle superpositionsexperimentally. In this work, we suggest simple setups, which resortto neither any extra quantum resources nor controlled-Hadamard gates, toobserve such superpositions as well as entanglement-separabilitysuperpositions with tunable entanglement degree. The suggested setups canalso serve as an interaction-free method to detect partially absorbingobjects.